FDI, Unemployment, and Welfare in the Presence of Agricultural Dualism: A Three-Sector General Equilibrium Model (The Pakistan Development Review, 2010)
The present paper uses a three-sector general equilibrium framework to examine the effect of Foreign Direct Investment (FDI) on unemployment and welfare in laboursurplus economies in the post-globalisation era. We show that the expansion of landhungry export-oriented agricultural sector through FDI accentuates the problem of urban unemployment in the presence of sticky urban wage and agricultural dualism. We also note that multiple cross-effects and factor specificity play an important role in determining change in output composition and welfare in the wake of the inflow of foreign capital. JEL classification: F16, F21 Keywords: Agricultural Dualism, FDI, Unemployment, Welfare